2002
DOI: 10.1677/joe.0.1750625
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of the growth hormone secretagogue, L-692,585, on isolated porcine somatotropes

Abstract: The effects of a GH secretagogue, L-692,585 (L-585), and human GH-releasing hormone (hGHRH) on calcium transient and GH release were investigated in isolated porcine pituitary cells using calcium imaging and the reverse hemolytic plaque assay (RHPA). Somatotropes were functionally identified by the application of hGHRH. All cells that responded to hGHRH responded to L-585 application. Perfusion application of 10 µM hGHRH and L-585 for 2 min resulted in an increase in intracellular calcium concentrations ([Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 34 publications
(39 reference statements)
3
23
0
Order By: Relevance
“…The increase in [Ca 2+ ] i evoked by leptin in porcine somatotropes is likely to be accompanied by an elevated GH release. In previous experiments on isolated porcine somatotropes with simultaneous measurements of GH release and calcium transients, we have shown that L-692,585, a nonpeptidyl GHS, evoked an increase in [Ca 2+ ] i that coincided with GH release [40]. In addition, it has been shown that leptin stimulates the basal GH release from cultured porcine somatotropes [30, 36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase in [Ca 2+ ] i evoked by leptin in porcine somatotropes is likely to be accompanied by an elevated GH release. In previous experiments on isolated porcine somatotropes with simultaneous measurements of GH release and calcium transients, we have shown that L-692,585, a nonpeptidyl GHS, evoked an increase in [Ca 2+ ] i that coincided with GH release [40]. In addition, it has been shown that leptin stimulates the basal GH release from cultured porcine somatotropes [30, 36].…”
Section: Discussionmentioning
confidence: 99%
“…The tissue was transferred to sterile cold (4°C) DMEM-0.1% BSA medium. Primary cell cultures from anterior pituitary glands were established using a method previously employed in our laboratory [40]. Tissue from 4 animals was incubated for 50 min at 37°C in 2 ml of EBSS papain solution (1.54 mg/ml).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tissue was transferred to a sterile cold (4°C) DMEM-0.1% BSA medium. Primary cell cultures from anterior pituitary glands were established using a method previously employed in our laboratory with neonatal pig anterior pituitary tissue [11]. Tissue from 3 chickens was incubated for 50 min at 37°C in 2 ml of EBSS-papain solution (1.54 mg/ml).…”
Section: Methodsmentioning
confidence: 99%
“…The present studies examine the response of individual somatotropes to secretagogues. The technique of loading pituitary cells with fura-2/AM followed by radiometric imaging [10, 11] allows determination of secretagogue-induced changes in intracellular calcium concentrations ([Ca 2+ ] i ) in individual cells . …”
Section: Introductionmentioning
confidence: 99%